Barriers Preventing Liver Transplantation in Canadians with HIV Infection – Perceptions of HIV Specialists - Curtis L Cooper; Joanne DeForest; John Gill; Richard Lalonde; on behalf of the Canadian HIV Trials Network (CTN) Co-Infection Core Group (Canadian Journal of Gastroenterology)
Liver transplantation is a life-saving procedure with demonstrated utility. There are accumulating data indicating that this procedure is helpful in HIV-infected patients as well. Liver transplantation is currently largely unavailable to those living with HIV in Canada. Understanding the obstacles to this procedure is the first step to increasing access. Between August 2005 and November 2005, HIV physicians, one from each Canadian HIV Trials Network site, were asked to complete a quantitative questionnaire on adult liver transplant access and need. Forty-six per cent (16 of 35) of sites responded. A median 20% of the nearly 12,700 HIV patients followed at these sites had concurrent liver disease (20% caused by hepatitis C virus, 5% caused by hepatitis B virus and 5% were alcohol-related). On average, two patients per site were thought to be appropriate candidates for liver transplant evaluation. Eighty per cent of respondents anticipated increased need for liver transplantation over the next five years. Organ supply was universally identified as the chief obstacle to transplantation in patients with HIV. Other key issues included risk of hepatitis C virus reinfection and transplant surgical team willingness. Based on these data, it is believed that these issues should be the focus of efforts designed to increase access to transplantation in Canadians with end-stage liver disease and concurrent HIV.